2007
DOI: 10.1007/s11661-007-9224-4
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Cold-Worked Structure on Electrochemical Properties of Austenitic Stainless Steels

Abstract: The effect of cold working on microstructure and structure and thereby on electrochemical behavior of metastable AISI 304L and stable AISI 316L austenitic stainless steels in two different solutions is presented here. The solution-annealed stainless steel (SS) plates were unidirectionally cold rolled at different rolling conditions (with or without interpass cooling and subzero temperature) up to 90 pct reduction in thickness. The X-ray diffraction (XRD) technique was employed to study textures and residual st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
19
0
1

Year Published

2008
2008
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 57 publications
(24 citation statements)
references
References 47 publications
4
19
0
1
Order By: Relevance
“…These inferences point out the lack of a direct correlation between the volume fraction of the α′-martensite phase and the corrosion behavior of 304 SS subjected to SMAT. Ravi Kumar et al have also reported the absence of a direct correlation between the pitting potentials and the volume fraction of α′-martensite phase when 304L SS is subjected to cold deformation from 0 to 90%. Barbucci et al have reported that the plasticity of the material could modulate the internal stresses and hence the reactivity of the material does not solely depend on the absolute amount of martensite phase.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…These inferences point out the lack of a direct correlation between the volume fraction of the α′-martensite phase and the corrosion behavior of 304 SS subjected to SMAT. Ravi Kumar et al have also reported the absence of a direct correlation between the pitting potentials and the volume fraction of α′-martensite phase when 304L SS is subjected to cold deformation from 0 to 90%. Barbucci et al have reported that the plasticity of the material could modulate the internal stresses and hence the reactivity of the material does not solely depend on the absolute amount of martensite phase.…”
Section: Discussionmentioning
confidence: 99%
“…Transformation of austenite to martensite phase during plastic deformation is likely to cause a deleterious influence on the corrosion resistance of 304 SS in chloride containing media. It has been reported that the martensite phase could be selectively dissolved at potentials closer to E corr , while at higher anodic potentials where the conditions are aggressive, dissolution of both austenite and martensite phases would occur . Hence, transformation of austenite to martensite phase could be responsible for the more negative E corr and a higher i corr observed for 304 SS treated using 5 and 8 mm ⌀ balls for 15, 30, 45, and 60 min, while the absence of passive film in these samples is due to the dissolution of both phases at higher anodic potentials.…”
Section: Discussionmentioning
confidence: 99%
“…Actually, deep rolling under cryogenic cooling improves the corrosion behavior of the AISI 304L stainless steel machined surfaces, comparatively to the dry condition, for high deep rolling speeds only. This issue is discussed in the following based on results of previous investigations establishing that the corrosion behavior of metallic components is linked to many factors such as temperature, surface topography, microstructure, strain-induced martensite, surface hardening, residual stress, or a combination of thereof [3,7,34,35].…”
Section: Discussionmentioning
confidence: 99%
“…However, it was seen that the corrosion behavior of the AISI 304L samples deep rolled under these conditions is significantly improved. Kumar et al [35] pointed out that the pitting potential changes of cold-worked 304 in 0.1 NaCl cannot be mainly related to the straininduced martensite but also to the effect of surface roughness, residual stresses, crystallographic structure or to combined effects of these parameters. In the present work, it is found that deep rolling at speeds of 75 m/min and 120 m/min, under cryogenic cooling, results in a significant improvement of the surface quality characterized by the reduction of surface roughness (Column A of Table 5).…”
Section: Discussionmentioning
confidence: 99%
“…Corresponding studies showed a deterioration [ 22–28 ] or improvement [ 29–32 ] of the corrosion resistance, which could even be reversed as the degrees of deformation increased. [ 14,33–36 ]…”
Section: Introductionmentioning
confidence: 99%